Road infrastructure design towards passenger ride comfort for autonomous public transport - Nguyen Van, Te Ron (Nanyang Technological University, 2020)
The rapid developments of smart technology and the vision to smart cities have led to parallel developments of various innovative transport means. Among them, road-based autonomous public transport (APT) is being planned, designed and developed worldwide such as the Dynamic Autonomous Road Transit (DART) in the city of Singapore. Innovative vehicle configuration and operation in the APT shall demand new requirements for design and construction of the infrastructure concerning the ride comfort of onboard passengers. This study aims at supporting the required update of guidelines for the design of roadway (e.g. horizontal alignment design), for vehicle speed recommendation along existing infrastructure and for pavement maintenance concerning passenger ride comfort in which DART is considered as a case study for APT application. Bottom-up and top-down approaches are used, in which the former method uses existing bus vehicles and network as a base-line reference while the latter method is based on APT’s vehicle specification and operation. At first, this study starts with a comprehensive review of ride comfort thresholds, recent approaches to evaluate passenger ride comfort onboard and to assess road surface irregularity, where research gaps are pointed out for further study. The interaction between passenger-vehicle-pavement is studied through numerical analysis. Given the similarities between regular bus and APT, the former system has been investigated and detailed bus mathematical models are constructed and validated to evaluate the pavement quality that affects passenger ride comfort. Based on the comparison of different bus models regarding their simulation complexity and performance, a refined Bus Ride Index (BRI) is proposed as a key achievement of this research study. At the same time, regression relationships are established between road geometrical design (e.g. horizontal curve radius) and passenger perceptions at different postures onboard the bus. Herein, experimental study with analytical analysis is carried out to evaluate principal factors (e.g. lateral acceleration, lateral jerk and duration of turning movement) affecting passenger-vehicle-road interaction and ride discomfort based on existing bus fleet and road network. Finally, the DART concept is examined from different perspectives such as network analysis, traffic operation and road infrastructure design. The findings indicate that research on geometry design and road maintenance based on passenger ride comfort for APT is important to support the new vehicle concept. In the urban context, while road geometry concerning the horizontal curve is contributing to the upper range (uncomfortable, very uncomfortable to extremely uncomfortable), road roughness is the principal factor affecting passenger ride quality in the lower range of discomfort (not uncomfortable, a little uncomfortable, fairly uncomfortable to uncomfortable). The developed BRI offers a faster, inexpensive, convenient and more suitable method for evaluating bus lane roughness regarding passenger ride comfort and can be used as a supporting measure for the conventional Pavement Management System using Automated Pavement Profiler. From the experimental study, the newly established ride comfort thresholds provide the recommendations for vehicle speeds within turning curves, as well as recommendations for the design of horizontal curves that ensure passenger ride comfort.